Rational design of colloidal core/shell quantum dots for optoelectronic applications - Xianglong Huang; Xin Tong; Zhiming Wang (Journal of Electronic Science and Technology, 2020)
Colloidal core/shell quantum dots (QDs) are promising for solar technologies because of their excellent optoelectronic properties including tunable light absorption/emission spectra, high photoluminescence quantum yield (PLQY), suppressed Auger recombination, efficient charge separation/transfer and outstanding photo-, thermal-/chemical stability. In this review, engineered core/shell QDs with various types of band structures and corresponding device performance in luminescent solar concentrators (LSCs), light-emitting diodes (LEDs), solar-driven photoelectrochemical (PEC) devices and QDs-sensitized solar cells (QDSCs) are summarized. In particular, the applications of interfacial layer engineering and eco-friendly, heavy metal-free core/shell QDs in optoelectronic device are highlighted. Finally, strategies towards the developments and practical perspectives of core/shell QDs are briefly mentioned to offer guidelines for achieving prospective high-efficiency and long-term stable QD devices.